2004
DOI: 10.1097/00008390-200402000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic expression of nm23 predicts the potential for cerebral metastasis in patients with primary cutaneous melanoma

Abstract: The nm23 gene is a putative tumour and metastasis suppressor gene. A number of studies have found that reduction of its expression is associated with increased metastatic potential in several human malignancies. Similarly, clinical studies have shown correlation between reduced nm23 protein expression and a poor prognosis. The aim of this study was to determine if a relationship exists between nm23 expression in primary cutaneous melanomas with or without cerebral metastases. Paraffin-embedded tissues were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In lung carcinoma cell lines, increased NME1 expression (Nie et al, 2008) and NME1 silencing (Zhao et al, 2013) decreased invasion and increased TGFβ-induced epithelial mesenchymal transition, respectively. This correlation was also found by immunohistochemical studies (Lee et al, 1996;Sarris et al, 2004;Ferrari et al, 2007), one including more than 100 patients (McDermott et al, 2000). However, other studies, including fewer cases, concluded to a lack of correlation (Easty et al, 1996;Saitoh et al, 1996;van den Oord et al, 1997).…”
Section: Notesupporting
confidence: 62%
“…In lung carcinoma cell lines, increased NME1 expression (Nie et al, 2008) and NME1 silencing (Zhao et al, 2013) decreased invasion and increased TGFβ-induced epithelial mesenchymal transition, respectively. This correlation was also found by immunohistochemical studies (Lee et al, 1996;Sarris et al, 2004;Ferrari et al, 2007), one including more than 100 patients (McDermott et al, 2000). However, other studies, including fewer cases, concluded to a lack of correlation (Easty et al, 1996;Saitoh et al, 1996;van den Oord et al, 1997).…”
Section: Notesupporting
confidence: 62%
“…Melanoma cells transfected with KiSS-1 showed significant decrease in metastatic ability [76]. Melanomas with low nm23 expression were highly predisposed to develop metastases to the brain, suggesting the predictive role of NM23 in tumor metastasis [77].…”
Section: Brain Metastasesmentioning
confidence: 99%
“…In addition to experimental evidence demonstrating that downregulation of metastasis suppressor gene function correlates to increased metastatic burden [126,127,[171][172][173][174], there is growing clinical evidence that reduction in the expression of a metastasis suppressor gene can be linked to the presence of metastases [149,150,[174][175][176][177][178][179][180][181][182][183][184][185][186]. Furthermore, measurement of the expression of a metastasis suppressor gene may prove a useful indicator for monitoring the response to treatment [187][188][189].…”
Section: Future Perspective and Clinical Utilitymentioning
confidence: 99%